A novel cross-flow honeycomb bionic carrier promotes simultaneous nitrification, denitrification and phosphorus removal in IFAS system: Performance, mechanism and keystone species. (15th October 2022) - Wu, Tong; Ding, Jie; Yang, Shan-Shan; Zhong, Le; Liu, Bing-Feng; Xie, Guo-Jun; Yang, Fan; Pang, Ji-Wei; Ren, Nan-Qi
Highlights: A novel cross-flow honeycomb bionic microbial carrier (CF) was developed. CF presented higher nitrogen removal performance compared to CM. System with CF removed nitrate mainly through DGAOs. The microbial community assembly was driven by deterministic selection. CF formed different co-occurrence networks and keystone species than CM. Abstract: Simultaneously achieving efficient nitrogen (N) and phosphorus (P) removal without adding external carbon source is vital for carbon-neutral wastewater treatment. In this study, a novel cross-flow honeycomb bionic microbial carrier (CF) was developed to improve the efficiency of simultaneous nitrification, denitrification, and P removal (SNDPR) in an integrated fixed-film activated sludge (IFAS) system. A parallel laboratory-scale sequencing batch reactor with the commercialized microbial carriers (CM) (CM-IFAS) was performed as the comparative system for over 233 d The results demonstrated that CF-IFAS exhibited a more consistent N removal efficiency and better performance than CM-IFAS. In the CF-IFAS, the highest N and P removal efficiencies were 95.40% and 100%, respectively. Typical cycle analysis revealed that nitrate was primarily removed by the denitrifying glycogen-accumulating organisms in the CF-IFAS and by denitrifying phosphate-accumulating organisms in the CM-IFAS. The neutral community model showed that the microbial community assembly in both the reactors was driven by deterministic selection rather than stochastic factors. Compared to those in CM-IFAS, the microorganisms in CF-IFAS were more closely related to each other and had more keystone species: norank_f_norank_o_norank_c_OM190, SM1A02, Defluviicoccus, norank_f_ Saprospiraceae, and norank_f_Rhodocyclaceae . The absolute contents of the genes associated with N removal (bacterial amoA, archaeal amoA, NarG, NapA, NirS, and NirK) were higher in CF-IFAS than in CM-IFAS; the N cycle activity was also stronger in the CF-IFAS. Overall, the microecological environment differed between both systems. This study provides novel insights into the potential of bionic carriers to improve SNDPR performance by shaping microbial communities, thereby providing scientific guidance for practical engineering. Graphical abstract: Image, graphical abstract